A Critical Discourse Analysis of the Representation of Social Actors in the Debate Between Prabowo Subianto and Anies Baswedan on the Kompas TV YouTube Channel - Monica Syafitri; Liliana Muliastuti; Siti Ansoriyah; N. Lia Marliana (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2026)
This study aims to analyze the role of emoji in the construction of emotional meaning in digital communication, especially on the WhatsApp platform among teenagers. With the increasing use of instant messaging applications, emoji has become an integral part of digital communication used to express emotions that are difficult to convey through text alone. Through a quantitative approach with a survey method of 50 respondents, this study explores the pattern of emoji use, user perceptions of the function of emoji in clarifying emotions, and how social context influences the interpretation of emoji. The results show that the majority of respondents use emoji to clarify emotions (70% agree), consider messages without emoji to be incomplete (37% agree), and believe that emoji helps reduce misunderstandings in digital communication (64% agree). However, there is an awareness that the meaning of emoji can be ambiguous and is influenced by the context and relationship between the sender and recipient. This study contributes to the understanding of the dynamics of digital communication and the role of non-verbal elements in the construction of emotional meaning in the era of text-based communication.